INTRODUZINDO A ASTRONOMIA PARA ALUNOS DO ENSINO FUNDAMENTAL: uma abordagem geométrica - MENEZES, Márcio de Souza (2024)
In this work we make a differentiated approach on the teaching of astronomy for elementary school, using a geometric approach. We first discuss the Mathematical Tools where we will discuss the Rectangle Triangle: definition of this, sum of its internal angles and Pythagorean Theorem, and Similarity of Triangles and Trigonometric Functions (Cosine, Sine and Tangent). We discussed the issue of Making Astronomical Measures where we discuss about Astronomy: its definition, what it studies, its history, its importance, life cycle of stars, HR diagram, besides the First Measurements: the size of the Earth, the size of the Moon , the distance Earth-Moon, the distance Earth-Sun and the size of the Sun, the distance of the Sun to a star: The Method of the Parallax. In the final chapter we describe some practical activities to understand the first measurements.